SISTEM INFORMASI COMPANY PROFILE PADA TK AL-MADINAH BERBASIS WEBSITE - Indira Putri Shahne; Rizki Maulana; Saprudin (CV. Multi Kreasi Media, 2024)
In the modern era, information dissemination has begun to utilize various technologies, and society as a whole relies on the internet to search for the information they need, ranging from clothing, buying and selling houses, private vehicles, and especially information about schools on websites. Currently, TK Al-Madinah still uses the method of distributing brochures or utilizing social media to provide information and promote the school. This research aims to develop and implement a website-based Company Profile Information System for TK Al-Madinah. This information system is designed to provide comprehensive and easily accessible information about the school's profile to parents, prospective students, and the general public. The research begins by analyzing the needs and goals of TK Al-Madinah in building an effective and efficient Company Profile. Subsequently, we design and develop a website-based system using the latest web development technologies. During the development process, we implement responsive design principles to ensure that the Company Profile can be accessed through various devices such as desktops, laptops, tablets, and smartphones. We also prioritize data security by implementing appropriate security mechanisms to protect sensitive information. After the development is completed, we conduct testing and evaluation of the system using simulated users and involved stakeholders. The evaluation results indicate that this Company Profile Information System successfully meets the needs and expectations of the users.